Photoelectrocatalytic Degradation of Organic Pollutants in Aqueous Solution Using a Pt-TiO2 Film - Chun He; Mudar Abou Asi; Ya Xiong; Dong Shu; Xiangzhong Li (International Journal of Photoenergy)
A series of Pt-TiO2 films with nanocrystaline structure was prepared by a procedure of photodeposition and subsequent dip-coating. The Pt-TiO2 films were characterized by X-ray diffraction, scanning electronic microscope, electrochemical characterization to examine the surface structure, chemical composition, and the photoelectrochemical properties. The photocatalytic activity of the Pt-TiO2 films was evaluated in the photocatalytic (PC) and photoelectrocatalytic (PEC) degradation of formic acid in aqueous solution. Compared with a TiO2 film, the efficiency of formic acid degradation using the Pt-TiO2 films was significantly higher in both the PC and PEC processes. The enhancement is attributed to the action of Pt deposits on the TiO2 surface, which play a key role by attracting conduction band photoelectrons. In the PEC process, the anodic bias externally applied on the illuminated Pt-TiO2 films can further drive away the accumulated photoelectrons from the metal deposits and promote a process of interfacial charge transfer.